2020
DOI: 10.1007/s00402-020-03564-7
|View full text |Cite
|
Sign up to set email alerts
|

Stable clinical long term results after AMIC in the aligned knee

Abstract: Introduction The aim of this study was to report a long-term follow-up of patients treated with autologous matrix-induced chondrogenesis (AMIC) for full-thickness chondral and osteochondral defects of the femoral condyle or patella combined with the correction of lower limb malalignment or patellar tracking if indicated. Methods Thirty-three patients (thirty-four knees) were treated surgically for chondral and osteochondral cartilage defects of the knee joint. Regarding the origin of the lesion, patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…However, since bone marrow appears especially promising judging by the few cases of this study, CartiScaff could be particularly favourable for bone marrow-based one-step procedure (e.g. augmented microfracture), and further improve the already promising results observed in clinical studies [74] .…”
Section: Discussionmentioning
confidence: 74%
“…However, since bone marrow appears especially promising judging by the few cases of this study, CartiScaff could be particularly favourable for bone marrow-based one-step procedure (e.g. augmented microfracture), and further improve the already promising results observed in clinical studies [74] .…”
Section: Discussionmentioning
confidence: 74%
“…Only 2 cases (14.3%) underwent concomitant corrective surgery with 1 open lateral release and 1 MPFL reconstruction, yet the authors did not specify the anatomy or clinical finding of the patellar instability. Kaiser et al 50 reported stable long-term clinical improvement with a mean Lysholm score of 85 and VAS of 2.3 among the retropatellar subcohort (n = 12) with 1 failure (revision total knee arthroplasty) at a mean follow-up of 9.3 years after AMIC. In this study, all patients with retropatellar AMIC had concomitant corrective surgery for patellar instability with transfer of the tibial tubercle, lateral release and reinforcement of the vastus medialis muscle.…”
Section: Discussionmentioning
confidence: 99%
“…So far, clinical results of AMIC for retropatellar cartilage lesions have only been reported in small case series, studies with short-term follow-up or as a part of studies investigating AMIC for the entire knee joint without thorough subanalysis. [23][24][25][26][27]50 D'Hollander et al 25 reported a case-series of 10 patients after AMIC for PF cartilage lesions with a follow-up of 24 months showing significant clinical improvement. Functional outcomes, however, were lower compared with the current study with a reported mean postoperative Kujula score of 59.8 versus 71.3 and total KOOS of 243.9 versus 343.4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traumatic injuries and degenerative changes of the knee joint are the most common cause of disability among all ages, causing reduced quality of life (QoL) [1,2]. Therefore, improving patient's QoL and symptoms are key objectives for surgery to treat knee disorders [3][4][5][6][7][8]. As a result, numerous injury-specific rating scales have been utilized in an attempt to enable the assessment of patient's health status, associated knee impairments and treatment effects [9].…”
Section: Introductionmentioning
confidence: 99%